Объяснение:
1) Mg(NO3)2 + 2KOH = Mg(OH)2 + 2KNO3
Mg(2+) + 2NO3(-)+ 2K(+)+ 2OH(-) = Mg(OH)2 + 2K(+)+ 2NO3(-)
Mg(2+) + 2OH(-) = Mg(OH)2
2) AlCl3 + 3NaOH = Al(OH)3 + 3NaCl
Al(3+) + 3Cl(-)+ 3Na(+) + 3OH(-)= Al(OH)3 +3Na(+)+ 3Cl(-)
Al(3+) + 3OH(-)= Al(OH)3
3) H2SO4 + CaCO3 = CaSO4 + CO2 + H2O
2H(+)+ SO4(2-) + CaCO3 = CaSO4 + CO2 + H2O
4) Na2SO3 + 2HCl = 2NaCl + SO2 + H2O
2Na(+) + SO3(2-) + 2H(+) + 2Cl(-) = 2Na(+)+ 2Cl(-) + SO2 + H2O
SO3(2-) + 2H(+)= SO2 + H2O
5) Al(OH)3 + 3HNO3 = Al(OH)3 + 3H2O
Al(OH)3 + 3H(+)+ 3NO3(-) = Al(OH)3 + 3H2O
Объяснение:
1) Mg(NO3)2 + 2KOH = Mg(OH)2 + 2KNO3
Mg(2+) + 2NO3(-) + 2K(+) + 2OH(-)= Mg(OH)2 + 2K(+)+ 2NO3(-)
Mg(2+) + 2OH(-) = Mg(OH)2
2) AlCl3 + 3NaOH = Al(OH)3 + 3NaCl
Al(3+) + 3Cl(-)+ 3Na(+) + 3OH(-) = Al(OH)3 + 3Na(+)+ 3Cl(-)
Al(3+) + 3OH(-)=Al(OH)3
3) H2SO4 + CaCO3 = CaSO4 + CO2 + H2O
2H(+) + SO4(2-) + CaCO3 = CaSO4 + CO2 + H2O
4) Na2SO3 + 2HCl = 2NaCl + SO2 + H2O
2Na(+) + SO3(2-) + 2H(+)+ 2Cl(-)= 2Na(+) + 2Cl(-) + SO2 + H2O
SO3(2-) + 2H(+)= SO2 + H2O
5) Al(OH)3 + 3HNO3 = Al(NO3)3 + 3H2O
Al(OH)3 + 3H(+)+ 3NO3(-)= Al(3+) + 3NO3(-) + 3H2O
Al(OH)3 + 3H(+)= Al(3+) + 3H2O
Объяснение:
3 моль Х моль
Fe3O4 + 4H2 = 3Fe + 4H2O
n=1 моль n=3 моль
3 моль Fe3O4 - Х моль Fe
1 моль Fe3O4 - 3 моль Fe
n(Fe) = 3 * 3 / 1 = 9 моль